2015
DOI: 10.1088/0954-3899/42/4/045107
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dissipation in the tilting degree of freedom from four-dimensional Langevin dynamics of heavy-ion-induced fission

Abstract: A four-dimensional dynamical model based on Langevin equations was applied to calculate a wide set of experimental observables for heavy fissioning compound nuclei. Three collective shape coordinates plus the tilting coordinate were considered dynamically from the ground state deformation to the scission into fission fragments. A modified one-body mechanism for nuclear dissipation with a reduction coefficient ks of the contribution from a ‘wall’ formula was used for shapes parameters. Different possibilities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…1 in order not to complicate figure. Our investigations [16] show that only the anisotropy of fission fragment angular distribution is dependent on both k s and γ K values, as it was found in previous investigation with heavy compound nuclei [6]. The comparison of theoretical 4D calculations with experimental data for the 200 Pb is presented in fig.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…1 in order not to complicate figure. Our investigations [16] show that only the anisotropy of fission fragment angular distribution is dependent on both k s and γ K values, as it was found in previous investigation with heavy compound nuclei [6]. The comparison of theoretical 4D calculations with experimental data for the 200 Pb is presented in fig.…”
supporting
confidence: 80%
“…After appearance of the neck in nuclear shape the γ const K value is joined smoothly with γ neck K (q), which was obtained in Refs. [5,16]. The third one is given by equation…”
mentioning
confidence: 99%
“…Recent theoretical dynamical 4D Langevin calculations [61,63,159,[212][213][214] realized the pure dynamical treatment of the K-mode relaxation process. The investigations were made for light, medium and heavy compound nucleus formed in the heavy ion collisions (from 162 Yb to 264 Rf).…”
Section: Angular Distribution Within 4d Langevin Dynamicsmentioning
confidence: 99%
“…Above-mentioned recent works [63,159,213,214] demonstrated that the impact of the dissipation coefficient for shape parameters (k s ) and the one for the Kmode (γ K ) on the calculated observables can be selec-tively probed. The nuclear viscosity with respect to nuclear shape parameters influences the emitted particle multiplicities (n pre ), the fission fragment MED parameters, and the angular distribution of fission fragments.…”
Section: Angular Distribution Within 4d Langevin Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation